PD-1 signaling modulates interferon-γ production by Gamma Delta (γδ) T-Cells in response to leukemia. (4th March 2019) - Hoeres, Timm; Holzmann, Elisabeth; Smetak, Manfred; Birkmann, Josef; Wilhelm, Martin
ABSTRACT: Gamma delta (γδ) T-cell based immunotherapy is a promising concept for the treatment of hematologic malignancies. Not only in vitro but also in early phase clinical trials, zoledronic acid (Zol) and interleukin-2 (IL-2) have been successfully used to activate human γδ T-cells and to induce clinical anti-tumor effects. Aiming to improve the effectiveness of future γδ T-cell based immunotherapies against leukemia, we analyzed the impact of programmed cell death protein 1 (PD-1) signaling, on the different phases of γδ T-cell activation, of proliferation, production of anti-tumor cytokines and cytotoxic function in vitro . PD-1 expression was found significantly upregulated between day 2 and day 4 following stimulation with Zol and IL-2. However, proliferation or expression of activation markers of γδ, αβ and NK-cells are not altered by additional PD-1 blockade. Pembrolizumab increases interferon-γ (IFN-γ) production in γδ T-cells upon direct stimulation with Zol and in response to Zol treated primary acute myeloid leukemia (AML) cells by approximately 57% and 30%, respectively. Zol sensitized primary AML cells also induce PD-1 expression in co-cultured γδ T-cells and such PD-1(+) cells contain more IFN-γ. In contrast, PD-1 blockade does not have a significant effect on direct cell dependent lysis of leukemia cells by γδ T-cells. This study demonstrates that PD-1 blockade impacts cell dependent cytotoxicity and cytokine production in response to leukemia cells differently. While Pembrolizumab did not increase cell lysis of stimulated and expanded γδ T-cells, it induces significant upregulation of the potent pro-inflammatory and anti-tumor cytokine IFN-γ, which might facilitate anti-leukemia effects.